Systematic analysis of missed colorectal cancer cases and common pitfalls in diagnosis. Issue 4 (28th January 2015) - Vaughan-Shaw, P G; Aung, M; Knight, H; Williams, T; Borley, N R; Wheeler, J M D
Abstract : Background: Missed colorectal cancer on endoscopic or radiological investigations may delay diagnosis and impact outcome. This study audits incidence of previous investigations in patients with colorectal cancer, considers outcome in 'missed' cancer cases and examines the diagnostic pathway in the derived case series to identify common pitfalls in diagnosis. Methods: Patients diagnosed with colorectal cancer in 2011 at a single National Health Service (NHS) Trust were reviewed. Incidence of endoscopic and radiological investigations in the 3 years preceding diagnosis and outcome data were collected. Cases of prior investigation not leading to diagnosis were considered 'missed' cancers and survival compared with 'detected' cases. The diagnostic pathway in each 'missed' case was reviewed. Results: 395 colorectal cancer cases were studied. Eighteen (4.6%) patients underwent previous investigation including colonoscopy (n=4), flexible sigmoidoscopy (n=5), barium enema (n=5) and diagnostic abdominal CT scan (n=12), median 708 days prior to diagnosis. Previous investigation predicted reduced overall and disease-free survival (HR 2.07, p=0.04 and HR 2.66, p<0.0001), after age and gender adjustment. Ten different categories termed 'pitfalls' were derived from analysis of the diagnostic pathway. These included CT scanning for abdominal pain without further investigation (n=7), rectosigmoid cancer following a previous diagnosis of diverticular disease (n=4) and incomplete diagnostic investigations without adequate follow-up (n=3). Conclusions: A proportion of patients diagnosed with colorectal cancer have previously been investigated for gastrointestinal symptoms and survival appears reduced in these patients. Regular audit and analysis of previous investigations can identify common pitfalls in diagnosis, which should be used to inform training and improve practice.